A COMPARATIVE STUDY OF BODY COMPOSITION AND SOMATOTYPE OF GOVERNMENT SCHOOL AND PRIVATE SCHOOL BOYS - Dr Alok Kumar Pandey (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Tremendous urbanization and mechanization of daily routines almost everywhere seem to have resulted not only in ‘hurrying and scurrying’ but also depriving people of natural vitality, vigor, muscular power and prowess which is so essential for a purposeful life. “The body must be vigorous in order to obey the soul; a good servant ought to be robust. The weaker the body, the more it commands, the stronger it is, the better it obeys. In order to think, we must exercise our limbs, our senses and our organs, which are the instruments of our intelligence. In order to derive all the advantages possible from these instruments, it is necessary that the body furnishes them should be robust and sound”. Body type has an important role in different sports activities. Good body compositions and physical characteristics help a sportsmen to do the best in sports. Systematic physical activity and athletic training can change body composition in a characteristic way. Exercise will increase the percentage of muscle in the total body composition and decrease the percentage of fat. Muscularity is one of the important factors, which assists the sportsperson to increase performance by producing more energy during the sports activities.